PELATIHAN PRANIKAH BAGI CALON PENGANTIN UNTUK MEMBENTUK KELUARGA SAKINAH DI KANTOR URUSAN AGAMA (KUA) KECAMATAN LEUWILIANG - Hilda Gustiani Rahman; Meilya, Ika Rizqi; Dewi, Ratna Sari (Comm-Edu (Community Education Journal), 2024)
Marriage is a sacred bond that requires thorough preparation to form a family that is sakinah, mawaddah, and rahmah. The high rates of divorce and domestic violence in Indonesia make premarital training very important. This study describes the implementation of premarital training at the KUA Kecamatan Leuwiliang, identifies supporting and inhibiting factors, and evaluates the outcomes of the training in forming sakinah families. Descriptive research is used to systematically depict the phenomenon. The training considers participant characteristics such as age, occupation, education, gender, and marital status. The materials are designed with relevant content, supported by competent tutors and adequate facilities. The main obstacles are budget limitations and low participant engagement. The results of the training show a positive impact in helping couples achieve a balance between worldly and spiritual needs. Alumni reported improvements in managing household finances, fulfilling social and psychological needs, as well as understanding and practicing religion within the family. However, alumni stated they have not yet become role models in society. Overall, premarital training at the KUA Kecamatan Leuwiliang is effective in helping couples achieve a harmonious balance in family life and forming sakinah families.